2016
DOI: 10.1371/journal.pone.0162400
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Oral Uracil-Tegafur with Leucovorin for Colorectal Cancer Liver Metastases: A Randomized Controlled Trial

Abstract: BackgroundThe high recurrence rate after surgery for colorectal cancer liver metastasis (CLM) remains a crucial problem. The aim of this trial was to evaluate the efficacy of adjuvant therapy with uracil-tegafur and leucovorin (UFT/LV).MethodsIn the multicenter, open-label, phase III trial, patients undergoing curative resection of CLM were randomly assigned in a 1:1 ratio to either the UFT/LV group or surgery alone group. The UFT/LV group orally received 5 cycles of adjuvant UFT/LV (UFT 300mg/m2 and LV 75mg/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(93 citation statements)
references
References 26 publications
4
88
1
Order By: Relevance
“…24e26 Postoperative chemotherapy was administered in patients who were candidates for adjuvant chemotherapy for the primary disease and patients assigned to clinical trials (UMIN000007787 and UMIN000000013, http://www.umin.ac.jp/ctr/index.htm). 27 The patients were followed up after resection by obtaining their history and performing a physical examination, laboratory evaluation, and axial imaging every 3e4 months for the first 2 years and every 4e6 months for the subsequent 3 years. When recurrences were diagnosed, the treatment strategy was decided by multidisciplinary consensus.…”
Section: Postoperative Follow-upmentioning
confidence: 99%
“…24e26 Postoperative chemotherapy was administered in patients who were candidates for adjuvant chemotherapy for the primary disease and patients assigned to clinical trials (UMIN000007787 and UMIN000000013, http://www.umin.ac.jp/ctr/index.htm). 27 The patients were followed up after resection by obtaining their history and performing a physical examination, laboratory evaluation, and axial imaging every 3e4 months for the first 2 years and every 4e6 months for the subsequent 3 years. When recurrences were diagnosed, the treatment strategy was decided by multidisciplinary consensus.…”
Section: Postoperative Follow-upmentioning
confidence: 99%
“…For patients with CLM, however, only limited evidence is available. To date, several studies have reported that adjuvant chemotherapy prolonged recurrence-free survival (RFS) after resection of CLM using 5-fluorouracil with leucovorin (5-FU/LV) [5], FOLFOX [4], or uracil-tegafur (UFT; Taiho Pharmaceutical Co. Ltd., Tokyo, Japan), an oral 5-FU preparation combining tegafur and uracil, with LV (UFT/LV) [6]; however, none of them could show the improvement in overall survival (OS). Nevertheless, because of the high relapse rate even after the curative resection of CLM [7], adjuvant chemotherapy has been widely used in actual clinical settings considering the resected tumor burden or the performance status of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Disease-free interval (DFI) from resection of primary lesion can be a factor estimating the risk of recurrence after heaptectomy for CLM [8]. However, definitions of synchronous and metachronous presentation vary among studies [4,6] and its influence on the efficacy of adjuvant chemotherapy has not well been studied so far.…”
Section: Introductionmentioning
confidence: 99%
“…However, their analysis of OS rather than DSS has made it di cult to interpret the result because senile weakness intolerant to adjuvant chemotherapy may have been directly associated with cancer-unrelated death in their assessment. Although administration of adjuvant chemotherapy after hepatectomy was not selected as a prognostic factor of DSS in univariate and multivariate analysis in the current study, a recent randomized trial demonstrated that adjuvant chemotherapy improves RFS in patients undergoing hepatectomy for CRLMs [27]. Additional studies are needed to investigate the prognostic impact of adjuvant chemotherapy, especially in older patients for whom the balance between therapeutic effect and toxicity is of great importance.…”
Section: Discussionmentioning
confidence: 87%